On potentials of ergodic Markov chains - Moskal'tsova, N. V.; Shurenkov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Two theorems on the existence of the potential of an ergodic Markov chain in an arbitrary phase space are proved.